Implementasi Pembelajaran Berbasis Proyek untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Perbaikan Peralatan Listrik - Shafir, Rionanda Maulana Muhammad; Usmeldi, Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study aims to determine whether project-based learning can improve student learning outcomes in the electrical installation subject for Grade XI TITL students at SMK Negeri 5 Padang. Project-based learning is still rarely used in the learning process, even though it enables students to engage directly with projects assigned by the teacher. The research method used in this study is a Quasi-Experimental Design, with a Nonequivalent Control Group Pretest-Posttest Design. The subjects were selected through purposive sampling, with the criterion that students had not yet learned the Competency Standard (KD) 5.2 on electrical equipment repair. The selected classes received a pretest to measure students' initial abilities, followed by the implementation of project-based learning, and finally a posttest. Pretest and posttest results were analyzed through a series of tests, including an independent t-test and effect size analysis. The analysis results showed an improvement in students' scores after implementing project-based learning in instruction.